ARTIFICIAL INTELLIGENCE IN VISUAL LEXICOGRAPHY: NEW APPROACHES TO VOCABULARY REPRESENTATION IN DIGITAL DICTIONARIES (Multidisciplinary Journal of Science and Technology, 2026)
The rapid development of artificial intelligence technologies has transformed numerous fields of human activity, including lexicography. Traditional dictionary compilation methods are increasingly being supplemented by intelligent systems capable of generating, organizing, and presenting lexical information through multimodal formats. This article investigates the role of artificial intelligence in visual lexicography and examines its impact on vocabulary representation in digital dictionaries. The study aims to identify innovative approaches employed by AI-powered visual dictionaries and to evaluate their potential contribution to language learning and lexicographic practice. Descriptive, comparative, and analytical methods were applied to examine contemporary digital lexicographic resources. The findings indicate that artificial intelligence facilitates automated image generation, semantic mapping, personalized vocabulary learning, and multimodal representation of lexical meaning. Furthermore, AI technologies enhance dictionary accessibility, adaptability, and user engagement. The study argues that the integration of artificial intelligence into visual lexicography contributes to the emergence of a new generation of digital dictionaries capable of functioning as intelligent knowledge systems. The article concludes that AI-assisted visual lexicography represents one of the most promising directions in contemporary lexicographic research.